1992
DOI: 10.1530/jrf.0.0950291
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from plasma progesterone concentrations for male-induced ovulation in the brush-tailed bettong, Bettongia penicillata

Abstract: Female brush-tailed bettongs, Bettongia penicillata, were housed with either an intact or vasectomized male or isolated from males in the peripartum period. Development of the quiescent corpus luteum formed at the post partum oestrus was initiated by removing the pouch young. Blood samples for analysis of plasma progesterone were collected from the females 2 days before removal of pouch young, daily for 5 or 6 days and then 2-3 times each week until 19 days after removal of pouch young. Plasma progesterone pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 16 publications
(29 reference statements)
2
13
0
Order By: Relevance
“…This second peak is coincident with a short-lived peak in plasma progesterone (0.8 ng ml~) on day 3, similar to that found by Jones and Rose (1992) at day 4 after removal of pouch young in the same species. Such a progesterone peak is also found in several other macropodid species (Cake et al, 1980;Hinds and Tyndale-Biscoe, 1982;Walker and Gemmell, 1983;Curlewis et al, 1987;Hinds and Smith, 1992). In the latter half of the oestrous cycle, the basal body temperature remains high before falling 2 days before oestrus.…”
Section: Discussionsupporting
confidence: 61%
“…This second peak is coincident with a short-lived peak in plasma progesterone (0.8 ng ml~) on day 3, similar to that found by Jones and Rose (1992) at day 4 after removal of pouch young in the same species. Such a progesterone peak is also found in several other macropodid species (Cake et al, 1980;Hinds and Tyndale-Biscoe, 1982;Walker and Gemmell, 1983;Curlewis et al, 1987;Hinds and Smith, 1992). In the latter half of the oestrous cycle, the basal body temperature remains high before falling 2 days before oestrus.…”
Section: Discussionsupporting
confidence: 61%
“…Nonetheless, male presence or interaction with females did not cause enhanced follicular development. Corpora lutea, a clear evidence of ovulation (Hinds andSmith 1992 in Malherbe et al 2004), were only found in mated females, consistent with Weir (1974), but not in females that only experienced body contact or even courtship to the males. Nearly all solitary subterranean rodents are induced ovulators, as most solitary mammals.…”
Section: Discussionsupporting
confidence: 55%
“…B. tropica lies between B. penicillata and B. gaimardi in this respect. Reproduction in B. penicillata is unusual in that females do not come into oestrus unless a mature male is present (Hinds & Smith, 1992;Smith, 1992), a phenomenon that has not been reported for either B. lesueur (Tyndale-Biscoe, 1968) or B. gaimardi (Rose, 1987). The present study did not address the question of male-induced oestrus in B. tropica and, considering the apparent variation within the genus, the situation in B. tropica requires clari®cation.…”
Section: Discussionmentioning
confidence: 65%